2017
DOI: 10.1002/job.2193
|View full text |Cite
|
Sign up to set email alerts
|

Supervisors' emotional exhaustion and abusive supervision: The moderating roles of perceived subordinate performance and supervisor self-monitoring

Abstract: Summary Drawing from conservation of resources theory, this study aims to create new knowledge on the antecedents of abusive supervision. Results across 2 independent field studies within a manufacturing context (Study 1) and a customer service context (Study 2) consistently demonstrated a 3‐way interaction pattern, such that supervisors' experiences of emotional exhaustion, perceived subordinate performance, and self‐monitoring were jointly associated with subordinates' abusive supervision perceptions. A supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 106 publications
(199 reference statements)
1
67
0
Order By: Relevance
“…De Cremer, Snyder, and Dewitte () conducted an experiment where they showed that high self‐monitors engaged in cooperative decision‐making even under low trust when social accountability was high (as the decisions participants made were going to be communicated to others in the experiment as opposed to being kept anonymous). Similarly, a recent study by Lam, Walter, and Huang () showed that emotional exhaustion triggers abusive behavior among supervisors lower on self‐monitoring and who are faced with an underperforming subordinate, suggesting that self‐monitoring may help supervisors suppress their aggression arising from emotional exhaustion. In a review paper on proactivity at work, Grant and Ashford () proposed that, when the situation involves accountability for the individual, self‐monitoring will be related to proactive behavior because of a desire to create favorable impressions on others.…”
Section: Self‐monitoring As a Moderatormentioning
confidence: 82%
“…De Cremer, Snyder, and Dewitte () conducted an experiment where they showed that high self‐monitors engaged in cooperative decision‐making even under low trust when social accountability was high (as the decisions participants made were going to be communicated to others in the experiment as opposed to being kept anonymous). Similarly, a recent study by Lam, Walter, and Huang () showed that emotional exhaustion triggers abusive behavior among supervisors lower on self‐monitoring and who are faced with an underperforming subordinate, suggesting that self‐monitoring may help supervisors suppress their aggression arising from emotional exhaustion. In a review paper on proactivity at work, Grant and Ashford () proposed that, when the situation involves accountability for the individual, self‐monitoring will be related to proactive behavior because of a desire to create favorable impressions on others.…”
Section: Self‐monitoring As a Moderatormentioning
confidence: 82%
“…In that regard, recent attention has been paid to leadership, in part because of its implications not just for the leader but also for others who work with the leader (e.g., Chi & Liang 2013, Hunter et al 2017, Schmitt et al 2016. For example, Lam et al (2017) report the results of two studies that find support for a nuanced response to emotional exhaustion whereby supervisors appear more likely to engage in abusive behavior toward subordinates (measured through the subordinates' evaluations of abusive supervisor behavior) when the supervisor is experiencing exhaustion, is relatively lower in self-monitoring, and the subordinate is performing lower than average. In effect, they argue that holding back the impulse to respond abusively to an underperforming employee requires self-regulatory resources (cf., DeWall et al 2007, Stucke & Baumeister 2006.…”
Section: Moving Beyond Stressmentioning
confidence: 99%
“…Specifically, when facing challenge stressors, individuals invest their limited pool of self-regulation resources to acquire potential development and growth; and when facing hindrance stressors, individuals should, even more, invest their limited pool of self-regulatory resources to control their negative emotions or overcome obstructive feelings. Thus, supervisors are less likely to exercise self-control to counteract abusive tendencies because work stressors result in constant consumption of limited selfregulatory resources (Liu et al, 2015;Lam et al, 2017). As such, it seems plausible that both challenge and hindrance stressors result in ego depletion, which in turn increases the likelihood of abusive supervision behavior.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%